First record of the mycophagous ladybird Psyllobora vigintiduopunctata on greenhouse cucumber plants in Crete (Greece) - Karataraki, K.; Goumenaki, E.; Raftakis, E.; Goutos, D.; Kapetanakis, E. (ENTOMOLOGIA HELLENICA, 2015)
In July 2014, in an organic greenhouse cucumber crop at the Farm of the Technological Educational Institute of Crete, at Heraklion, larvae and adults of Psyllobora vigintiduopunctata (L.) (Coleoptera: Coccinellidae) were observed feeding on hyphae of Podosphaera xanthii (Braun & Shishkoff) (Erysiphales: Erysiphacae), that had covered the cucumber leaves. The most common genus worldwide of mycophagous tribe Halyziini (Mulsant) is Psyllobora, which is known for its potential in the biological control of powdery mildew.